Pengelolaan Hubungan Kerja Kepala Sekolah dan Guru di Rintisan sekolah Bertaraf Internasional (Studi Situs di SMP N 1 Delanggu) - Satriawati, Rahma Widhi; , Prof. Dr. Bambang Sumardjoko, M. Pd (2017)
The objectives of the study are to: 1) describe the characteristics of headmaster leadership in building work relation between headmaster and teachers at SMP Negeri 1 Delanggu and 2) describe the characteristics of togetherness between headmaster and teachers at SMP Negeri 1 Delanggu. The study is qualitative study using ethnography design to understand view point of SMP Negeri 1 Delanggu community concerning work relation management of headmaster and teachers at international level prospective school. The data collecting techniques are observation, interview, and document. The data are analyzed by data reduction, data display, and drawing conclusion and verification. Result of the study shows that: 1) the characteristics of headmaster leadership in building work relation between headmaster and teachers are performance evaluation of each teachers, headmaster has note about characteristics of each teacher, perception that headmaster needs teachers in performing job becomes base in building work relation, headmaster conducts meeting to discuss problems, headmaster greatly supports teachers in improving their skills and competences, headmaster builds networks between the school and other institutions either in regional, national, or international level, outsourcing program to improve English and computer skills. 2) the characteristics of togetherness between headmaster and teachers are there is support as friends in performing duty, there is openess in accepting critics, opinion, inisiative, and creativity fpr school, there is good cooperation in preparing event in order to get best result, there is effective communication in discussing and taking decision, headmaster conducts interview to post teachers based on their ability, there is discussion of problems outside school problems, and there is high commitment and reward. Keywords: management, work relation, headmaster, teacher